2011
DOI: 10.1007/s11136-011-9857-z
|View full text |Cite
|
Sign up to set email alerts
|

Does the subjective quality of life of children with specific learning disabilities (SpLD) agree with their parents’ proxy reports?

Abstract: In the case of SpLD, the child's problem area, which is reflected in the KINDL(R) dimension of everyday functioning in school, seems to be an issue of controversial value that may be differentially perceived by children and their mothers. Further, it can be argued that as mothers seemed to perceive in a more negative way the child's QoL at school, they were at the same time attempting to counterbalance their reactions by overestimating the child's physical and emotional well-being. Besides differences, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 26 publications
8
45
1
1
Order By: Relevance
“…In contrast, other studies revealed HRQOL (sub)scale rankings that differed between children and parents. For instance, in the study on specific learning disorders, the ES for the self-rated 'school' subscale were not clinically meaningful, whereas parents rated this subscale in such a way as to produce the largest ES [31]. The authors provide multiple explanations for this discrepancy: like parents overemphasizing their child's difficulties in school, children underestimating their target problem to prevent themselves from stressful recognition, and children adjusting to their problem so no further limitations are experienced in the HRQOL subscale that targets academic functioning.…”
Section: Child Ratingsmentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, other studies revealed HRQOL (sub)scale rankings that differed between children and parents. For instance, in the study on specific learning disorders, the ES for the self-rated 'school' subscale were not clinically meaningful, whereas parents rated this subscale in such a way as to produce the largest ES [31]. The authors provide multiple explanations for this discrepancy: like parents overemphasizing their child's difficulties in school, children underestimating their target problem to prevent themselves from stressful recognition, and children adjusting to their problem so no further limitations are experienced in the HRQOL subscale that targets academic functioning.…”
Section: Child Ratingsmentioning
confidence: 94%
“…Some authors considered item overlapping as a possible explanation for this result [23; 25]. Furthermore, it is possible that parents may have over-emphasized the HRQOL aspect that is most closely related to the main problem their child has [31].…”
Section: Parent Ratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two review articles that mainly included physically ill or healthy children [10,11], as well as in studies among children with mental health problems [14][15][16][17][18][19][20][21][22], correlations and/or ICCs have ranged from poor to good.…”
Section: Introductionmentioning
confidence: 99%
“…When the means of self-and proxy ratings were compared, it was established that parents of physically ill children [11] as well as of children with mental disorders [14][15][16][17][18][19][20][21][22] rate most HRQOL domains (significantly) lower than the children themselves. With regard to non-clinical samples, Upton et al [11] proposed that this pattern was reversed (i.e., self-ratings \ parent ratings).…”
Section: Introductionmentioning
confidence: 99%